PENGENDALIAN HAMA PENGGEREK BATANG PADI Scirpophaga sp YANG MENYEBABKAN PENURUNAN PERTUMBUHAN TANAMAN PADI MASYARAKAT DESA PELAWI SELATAN KECAMATAN BABALAN - Mahyu Daniel; Murni Sri Rahayu; Mahrani Arfah; Rahim Partogi Siregar; Andina Mei Vani Lubis (Jurnal Pengabdian Mitra Masyarakat, 2022)
South Pelawi Village has the potential as a rice farmer whose commodity is rice, the rice owned by farmers in South Pelawi Village is rainfed rice where the irrigation is only obtained by rain or expects rain so that the risk of drought often occurs in the area during the dry season. In the land of farmers in Pelawi Darat, in the rice field agriculture sector, farmers have complaints which are pests, pests that interfere with rice plants belonging to farmers in South Pelawi village are rice stem borer (scirpophaga sp). Rice stem borer control is usually done by means of light traps, using insecticides, and the use of natural enemies. In this pest control activity, we use an insecticide made from the chemical fipronil which is the trademark Regent.